Evaluasi Pengelolaan Obat di Puskesmas Terminal Kota Banjarmasin Tahun 2021 - Sariah Sariah; Yodi Fernanda; Rahmi Annisa; Nashrul Wathan (BORNEO JOURNAL OF PHARMASCIENTECH, 2022)
Drug management at a public health center is an important indicator of the quality of pharmaceutical services as it determines the success of its management. Drug management activities at a public health service involve aspects of planning, requesting, receiving, storing, distributing, destroying, controlling, as well as recording and reporting. This activity aims to ensure that drugs can be managed optimally to ensure the correct amount and type of pharmaceutical supplies in an effort to achieve the goals set at various levels of the work unit. This research aimed to evaluate drug management at Terminal public health center in Banjarmasin. The parameters used were accuracy of drug planning, compatibility of available drug items with DOEN 2021, percentage of drugs not prescribed for 6 months, and ercentage of expired or damaged drugs. This research was a descriptive non-experimental research conducted qualitatively using retrospective data, namely RKO and LPLPO from the period of January–December 2021. The results showed the evaluation of drug management at Terminal public health center in Banjarmasin, respectively: accuracy of drug planning (68%), compatibility of available drug items with DOEN 2021 (54%), drugs not prescribed for 6 months (18%), and expired or damaged drugs (4%). Based on these results, it could be seen that the drug management system at Terminal public health center in Banjarmasin hasn’t met the established standards.